1986
DOI: 10.1007/bf00120907
|View full text |Cite
|
Sign up to set email alerts
|

Wind profile constants in a neutral atmospheric boundary layer over complex terrain

Abstract: The roughness height zc and the zero-plane displacement height d,, were determined for a region of complex terrain in the Pre-Alps of Switzerland. This region is characterized by hills of the order of 100 m above the valley elevations, and by distances between ridges of the order of 1 km; it lies about 20 to 30 km north from the Alps. The experimental data were obtained from radiosonde observations under near neutral conditions. The analysis was based on the assumption of a logarithmic profile for the mean hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 25 publications
3
42
0
2
Order By: Relevance
“…Th is is considerably higher than the value of 10% which is often taken as the thickness of the surface layer of a turbulent boundary layer. This is a confirmation of the earlier findings of Kustas and Brutsaert (1986) in the rugged terrain of the Swiss Fore-Alps. Evidently the rule-of-thumb of 10% is only applicable to surfaces with smaller roughness.…”
Section: Concluding Summarysupporting
confidence: 91%
See 1 more Smart Citation
“…Th is is considerably higher than the value of 10% which is often taken as the thickness of the surface layer of a turbulent boundary layer. This is a confirmation of the earlier findings of Kustas and Brutsaert (1986) in the rugged terrain of the Swiss Fore-Alps. Evidently the rule-of-thumb of 10% is only applicable to surfaces with smaller roughness.…”
Section: Concluding Summarysupporting
confidence: 91%
“…As a further illustration of the neutrality of profile, it should be possible to determine these parameters from the profile observations. However, rawinsonde data are usually quite noisy as a result not only of turbulence (i.e., short-term sampling) but also of instrumental error (see also Kustas and Brutsaert, 1986). Therefore it is desirable to reduce the number of unknown parameters to the absolute minimum and to constrain the equation to ensure proper behavior.…”
Section: Description Of Experimentsmentioning
confidence: 99%
“…Observations (Grant and Mason, 1990;Kustas and Brutsaert, 1986) have shown that small hills tend to produce a logarithmic wind profile above themselves, typical of a large roughness length. Therefore, roughness length In the latter case, a drag force is applied in the Nature and Town tiles for the wind.…”
Section: Orographic Frictionmentioning
confidence: 99%
“…Wood and Mason, 1993) and field (e.g. Kustas and Brutsaert, 1986;Grant and Mason 1990) studies have supported the hypothesis that the equivalent homogeneous surface approach using effective parameters is valid for representing non-homogeneous surfaces. In fact, the effective parameter approach is inevitable to describe evaporation over an area in many cases, since the actual surface is almost always heterogeneous and it is impossible to describe every roughness obstacle on the surface in the equation to estimate evaporation.…”
Section: Introductionmentioning
confidence: 81%